PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA TERHADAP LOYALITAS KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA RS ‘AISYIYAH KUDUS - Wahyudi, Ricky (Jurnal Studi Manajemen Bisnis, 2023)
This study aims to analyze the effect of organizational culture and work environment on employee loyalty with job satisfaction as an intervening variable at RS ‘Aisyiah Kudus. The population in the study was 95 non-medical employee with a total sample of 76 employee with purposive sampling technique. Data collection using a questionnaire. Data analysis using SmartPLS. The results of this study concluded (1) Organizational culture has a positive and significant effect on job satisfaction at RS ‘Aisyiyah Kudus, (2) Work environment has a positive and significant effect on job satisfaction at RS ‘Aisyiyah Kudus, (3) Organizational culture has a positive and significant effect on employee loyalty at RS ‘Aisyiyah Kudus, (4) Work environment has a positive and significant effect on employee loyalty at RS Aisyiyah Kudus, (5) Job satisfaction has a positive and significant effect on employee loyalty at RS ‘Aisyiyah Kudus. Keywords: Organizational Culture, Work Environment, Job Satisfaction, Employee Loyalty